2007
DOI: 10.1159/000098469
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Anti-SSA Autoantibodies in Primary Sjögren’s Syndrome with Central Nervous System Involvement

Abstract: Background: Central nervous system involvement in primary Sjögren’s syndrome is a matter of controversy, and its diagnosis remains difficult. Methods: We report 3 patients with primary Sjögren’s syndrome and central nervous system involvement in whom we assessed intrathecal immunoglobulin G synthesis and the presence of cerebrospinal fluid anti-SSA and anti-SSB autoantibodies. Results: We found intrathecal immunoglobulin G synthesis and presence of cerebrospinal fluid anti-SSA autoantibodies in all patients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…Few studies reported routine CSF findings such as cell count, glucose, total protein level, and oligoclonal bands (OCBs) in case reports or small case series [4,[9][10][11][12][13] . In 1986, CSF cell count, total protein, and IgG profiles from 30 patients with CNS involvement due to Sjögren's syndrome were described [14] .…”
Section: Cerebrospinal Fluid Findings Inmentioning
confidence: 99%
“…Few studies reported routine CSF findings such as cell count, glucose, total protein level, and oligoclonal bands (OCBs) in case reports or small case series [4,[9][10][11][12][13] . In 1986, CSF cell count, total protein, and IgG profiles from 30 patients with CNS involvement due to Sjögren's syndrome were described [14] .…”
Section: Cerebrospinal Fluid Findings Inmentioning
confidence: 99%
“…Die Differenzierung zur MS ist nicht immer einfach. Hierbei hilft die Bestimmung der oligoklonalen Banden oder anti-Ro-Antikörper im Liquor [18]. Zur Abgrenzung gegenüber einer Neuromyelitis optica (NMO, bzw.…”
Section: Extraglanduläre Manifestationenunclassified
“…For patients reporting memory deficit, dementia or cognitive dysfunction, these white matter lesions are always present [ 32 , 43 48 ]. In one case of dementia, an Electroencephalogram (EEG) agreed with the SPECT findings above, identifying in the parietal lobes short runs of theta activities; symptoms improved with treatment of corticosteroids [ 49 ].…”
Section: Brain Lesionsmentioning
confidence: 99%
“…This same treatment for another patient worked and others in the study (treated with 5 to 10 mg daily of Donepezil) also saw improvement and ceased cognitive decline [ 45 ]. Treatment with hydroxychloroquine was also effective against memory and concentration deficits [ 48 ]; contrarily, L-dopa has not improved patient symptoms [ 47 ]. In this study, 12 patients (out of 20 pSjS patients) were found to have dementia- the majority of which had parietal lobe lesions by SPECT, but this statistic is skewed drastically from its occurrence in the average population, as the patients were chosen at a memory clinic.…”
Section: Brain Lesionsmentioning
confidence: 99%